Studi Etnobotani Tumbuhan sebagai Bahan Kerajinan di Desa Sekida Kabupaten Bengkayang - Susana, Stefany; Syamswisna, Syamswisna; Tenriawaru, Andi Besse (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The people of Sekida Village in Bengkayang Regency have a long tradition of using plants as handicraft materials. The urgency of this research is to find and record the wealth of local wisdom owned by the residents of Sekida Village, Bengkayang Regency. This research wants to find out more about the types of plants and plant organs that are used as handicraft materials, as well as their applications and production processes. The research was conducted for one month in Sekida Village, Bengkayang Regency (September 2022 – November 2022). Interviews, direct observation, careful record keeping, and plant assistance were all part of the data collection process in this descriptive study. This study involved 11 informants from craftsmen and village heads. Residents of Sekida Village, Bengkayang Regency, are known to use 20 different types of plants to make 19 types of handicrafts. Stems are the most commonly used plant components and the Arecaceae family plants are the most commonly used source of craft materials. Residents of Sekida Village, Bengkayang Regency mostly use rattan as a craft material.